2019
DOI: 10.3390/plants8050111
|View full text |Cite
|
Sign up to set email alerts
|

Natural Compounds That Modulate the Development of the Fungus Botrytis cinerea and Protect Solanum lycopersicum

Abstract: Botrytis cinerea is the causal agent of gray mold disease and is responsible for the loss of millions of dollars in crops in worldwide. Currently, this pathogen exhibits increasing resistance to conventional fungicides; therefore, better control methods and novel compounds with a more specific mechanism of action but without biocidal effects, are required. In this work, several natural compounds to control B. cinerea were analyzed in vitro. Detected effects were dependent on the stage of fungus development, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…One of the hosts is the tomato plant ( Solanum lysopersicum ), an important and widely used agricultural crop. So far, infection control was managed by chemical fungicides [ 56 ], which, in itself, proves to be a problem due to residues in tomato fruits and the risk of toxicity for consumers [ 57 , 58 ]. Additionally, recent evidence showed that B. cinerea has already acquired resistance to many of the commonly used fungicides [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the hosts is the tomato plant ( Solanum lysopersicum ), an important and widely used agricultural crop. So far, infection control was managed by chemical fungicides [ 56 ], which, in itself, proves to be a problem due to residues in tomato fruits and the risk of toxicity for consumers [ 57 , 58 ]. Additionally, recent evidence showed that B. cinerea has already acquired resistance to many of the commonly used fungicides [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the search for new methods to control B. cinerea, we previously evaluated the effect of several compounds on its growth. The results suggested a modulatory mechanism mediated by QS [12], which is a microbial communication mechanism extensively studied in bacteria, although it has now been reported in some yeasts and filamentous fungi [5]. Fungal development shows behavior with a high resemblance to the QS of bacteria, as they undergo a process of colonization, followed by pathogenesis, then there is virulence through the synthesis of toxins among other compounds, and finally, there is resistance by sporulation and the formation of a biofilm.…”
Section: Discussionmentioning
confidence: 86%
“…The disease severity was evaluated based on scale 0 to 4 as described by Rosero-Hernández et al [ 23 ] using the following scale: 0 = no visible symptoms of fruits (no infection); 1 = 1–25% inoculated area covered with slight necrotic and water-soaked lesion (mild infection); 2 = 26–50% of the inoculated area covered with necrotic, white to gray mycelia and water-soaked lesion (moderate infection); 3 = 51–75% of fruits are necrotic with spore mass appeared and water-soaked (severe infection); 4 = >76% necrotic tissue appears soft, watery and decayed (very severe).…”
Section: Methodsmentioning
confidence: 99%